Effect of parasitic entomophages in controlling plant lice pests in vegetable crops and their numbers - Kimsanbaev Khojimurad; Rustamov Adkham (E3S Web of Conferences, 2023)
The impact of pests and diseases on agricultural crops has been amplified due to global environmental changes, resulting in an estimated adverse effect of 1.4 trillion dollars, which is approximately 5% of the world's gross domestic product. Research was conducted on various species of parasitic entomophages, such as Aphidius matricaria Hal, Aphidius gifuensis Ashm, Lysiphlebus japonica Tokawa, Aphidius ervi Hal, Lysiphlebus fabarum Marsh, Lysiphlebus fritzmuelleri Mack, and Lysiphlebus testaceipes Creeson, to determine their efficacy in controlling plant lice. The biological efficiency of the parasite in Aphis craccivora was 52.5%. As well as Aphis gossypii Glow, Acyrthosiphon gossypii Glow. parasite infection of species was 42.1-38.4%. Praon volucre Hal parasite in Aphis craccivora was 49.6%. Aphis Gossypii Glow phytophage infestation was 56.3%, while Acyrthosiphon gossypii Glow plant aphid infestation with Praon volucre Hal was 42.4%.